Pain Location and Exacerbating Activities Associated with Treatment Success Following Basivertebral Nerve Ablation: An Aggregated Cohort Study of Multicenter Prospective Clinical Trial Data. (20th July 2022) - McCormick, Zachary L; Sperry, Beau P; Boody, Barret S; Hirsch, Joshua A; Conger, Aaron; Harper, Katrina; Lotz, Jeffrey C; Burnham, Taylor R
Abstract: Objective: Develop pain location "maps" and investigate the relationship between low back pain (LBP)-exacerbating activities and treatment response to basivertebral nerve radiofrequency ablation (BVN RFA) in patients with clinically suspected vertebral endplate pain (VEP). Design: Aggregated cohort study of 296 patients treated with BVN RFA at 33 centers in three prospective trials. Methods: Participant demographics, pain diagrams, and LBP-exacerbating activities were analyzed for predictors using stepwise logistic regression. Treatment success definitions were: (1) ≥50% LBP visual analog scale (VAS), (2) ≥15-point Oswestry Disability Index (ODI), and (3) ≥50% VAS or ≥15-point ODI improvements at 3 months post-BVN RFA. Results: Midline LBP correlated with BVN RFA treatment success in individuals with clinically-suspected VEP. Duration of pain ≥5 years (OR 2.366), lack of epidural steroid injection within 6 months before BVN RFA (OR 1.800), lack of baseline opioid use (OR 1.965), LBP exacerbation with activity (OR 2.099), and a lack of LBP with spinal extension (OR 1.845) were factors associated with increased odds of treatment success. Regressions areas under the curve (AUCs) were under 70%, indicative of low predictive value. Conclusions: This study demonstrates that midline LBP correlates with BVN RFA treatment success in individuals with VEP. While none of the regression models demonstrated strong predictive value, the pain location and exacerbating factors identified in this analysis may aid clinicians in identifying patients where VEP should be more strongly suspected. The use of objective imaging biomarkers (Type 1 and/or 2 Modic changes) and a correlating presentation of anterior spinal element pain remain the most useful patient selection factors for BVN RFA.